Smoke on the water: the interplay of fire and water flow on Everglades restoration. Issue 9 (1st November 2003) - Lockwood, Julie L.; Ross, Michael S.; Sah, Jay P.
Abstract : Recent research makes clear that much of the Everglade's flora and fauna have evolved to tolerate or require frequent fires. Nevertheless, restoration of the Everglades has thus far been conceptualized as primarily a water reallocation project. These two forces are directly linked by the influence of water flows on fire fuel moisture content, and are indirectly linked through a series of complex feedback loops. This interaction is made more complex by the alteration and compartmentalization of current water flows and fire regimes, the lack of communication between water and fire management agencies, and the already imperiled state of many local species. It is unlikely, therefore, that restoring water flows will automatically restore the appropriate fire regimes, leaving the prospect of successful restoration in some doubt. The decline of the Cape Sable seaside sparrow, and its potential for recovery, illustrates the complexity of the situation.